Anodic co-electrodeposition of hierarchical porous nano-SiO2+PbO2 composite for enhanced performance of advanced lead-carbon batteries. (March 2021) - Bao, Jinpeng; Lin, Nan; Dan, Yuanyuan; Gao, Weiqi; Liu, Zhiqiang; Lin, Haibo
Highlight: 1 Co-electrodeposition for SiO2 +PbO2 additive applied in LCB has been introduced. 2 SiO2 +PbO2 has excellent porous structure and great electrochemical performance. 3. SiO2 +PbO2 can facilitate ion transfer channels inside the active materials. Abstract: Silica and its compounds have attracted considerable attention because they own some unique features like great electrochemical stability in sulfuric acid solution and strong electrolyte storage capacity. In this paper, SiO2 +PbO2 powders with high specific surface area, hierarchical porous structure and good electrochemical performance have been prepared successfully via the facile anode co-electrodeposition. After adding these powders into the lead-carbon battery, this additive can build outstanding ion transfer channels inside the positive active material and thus advance the energy density and stability of the positive electrode via the enhancement of ionic diffusivity and the promotion of contact between ion and electrode. Comparing with the lead-carbon battery without this additive, the energy density of the modified battery is increased by 12% and the stability is enhanced by 10% after cycling 3000 times in HRPSoC. Graphical abstract: Image, graphical abstract